Hitler's Children Based on a Book by Gregor Ziemer - Ziemer, Gregor (Warner Archive Collection, 2015)
Tim Holt and Bonita Granville expose the Nazi corruption of German youth in this wartime shocker, based on Gregor Ziemer's best-selling book and directed by Edward Dmytryk (Murder, My Sweet). During the Memorial Day celebrations at the American Colony School run by Professor Nichols (Kent Smith), U.S. citizen and teacher Anna Muller (Granville) is arrested by the Gestapo. Finding her in a labor camp, Nichols turns to Anna's childhood boyfriend, SS Lieutenant Karl Bruner (Holt), who warns the professor not to interfere. Sentenced to be sterilized for refusing to bear children for the Fuhrer, Anna escapes from the camp, and Karl is forced to decide whether to help his old friend or carry out the dictates of Hitler. An exploitation picture that pulled no punches, "Hitler's Children" was the sleeper hit of the year and went on to become one of the highest-grossing films in RKO history. [www.amazon.com]